The Relationship Between Thyroid Function and the Prevalence of Type 2 Diabetes Mellitus in Euthyroid Subjects - Gu, Yeqing; Li, Huihui; Bao, Xue; Zhang, Qing; Liu, Li; Meng, Ge; Wu, Hongmei; Du, Huanmin; Shi, Hongbin; Xia, Yang; Su, Qian; Fang, Liyun; et al. (The journal of clinical endocrinology and metabolism, 2017)
Purpose:Thyroid hormones (THs) are primarily responsible for the regulation of energy balance and metabolism, suggesting that TH levels may contribute to the development of type 2 diabetes mellitus (T2DM). However, few studies have investigated the relationship between TH and T2DM in a general population. The aim of this study was to evaluate whether serum TH levels within the reference range are related to T2DM.Methods:A cross-sectional study (n = 15,296) was performed in Tianjin, China. Serum free triiodothyronine (FT3), free thyroxine (FT4), and thyroid-stimulating hormone (TSH) levels were measured by chemiluminescence immunoassay, and T2DM was defined according to the American Diabetes Association criteria. Multiple logistic regression models were used to assess the sex-specific relationships between FT3, FT4, FT3/FT4 ratios, and TSH quintiles and T2DM.Results:The prevalence of T2DM was 16.2% in males and 7.7% in females. In males, the multivariable-adjusted odds ratios (95% confidence interval) of T2DM for increasing quintiles of FT3, FT4, and FT3/FT4 ratios were 1.00, 0.75(0.63 to 0.89), 0.70(0.58 to 0.84), 0.63(0.52 to 0.76), 0.56(0.46 to 0.68; P for trend < 0.0001); 1.00, 1.05(0.87 to 1.27), 1.16(0.96 to 1.40), 1.09(0.90 to 1.31), 1.29(1.07 to 1.56; P for trend = 0.01); and 1.00, 0.69(0.58 to 0.83), 0.72(0.60 to 0.86), 0.59(0.48 to 0.71), and 0.55(0.46 to 0.66; P for trend < 0.0001), respectively. Similar results also were observed in females. In contrast, a strong negative correlation between TSH and T2DM was observed in males, but not in females.Conclusions:This study demonstrated that decreased FT3, FT3/FT4 ratios, and increased FT4 levels are independently related to a higher prevalence of T2DM in both males and females, and TSH is inversely related to T2DM in males only.This paper is the first report showing that serum thyroid hormones and thyroid-stimulating hormone concentrations are related to the prevalence of type 2 diabetes mellitus in the general population.